EFFICACY OF KINESIO TAPING IN EARLY STAGE BREAST CANCER ASSOCIATED LYMPHEDEMA: A RANDOMIZED SINGLE BLINDED STUDY - (:unkn) unknown (LYMPHOLOGY, 2019)
This study was designed to evaluate the effectiveness of kinesio taping compared to compression garment in treatment of early stage breast cancer-associated lymphedema (BCAL). Patients between 18-70-years old who had unilateral stage 1 BCAL were randomized into group I kinesio taping (KT) and group II compression garment (CG) for this single blinded study. KT was applied with a lymphatic correction technique in three-four day intervals for four weeks. At the end of the fourth week, patients were suggested to wear CGs. Patients in group II were treated daily for 23-hours in CGs. Education, preventive measures, and exercises were given to both groups. All patients were evaluated before the treatment (TO), immediate post treatment (T1), and three months after treatment (T2). Circumference differences were measured between the extremities with a nonelastic tape at five levels. Additionally, shoulder range of motion (ROM) was measured, and pain, heaviness, and sensation of tightness were evaluated with a visual analog scale (VAS). Thirty-five patients with stage 1 BCAL were included and randomized to the KT (n= 16) and CG (n= 19) groups. Demographic data and baseline clinical characteristics were similar. Both groups had reductions in all levels of arm circumference differences at immediate post-treatment and three months after treatment. Pain, tightness, and heaviness scores significantly decreased for both groups at immediate post-treatment and third month. Patients in the KT group had significantly lower pain sores than patients in the CG group. Results demonstrated that both modalities had similar effects in the treatment of early stage BCAL. For patients with early stage BCAL, KT can be an alternative treatment to CG for patients who have difficulties in obtaining and wearing CGs.
Keywords: compression garment; lymphedema; breast cancer; kinesio taping; randomized clinical trial; CHRONIC VENOUS INSUFFICIENCY; QUALITY-OF-LIFE; POSTMENOPAUSAL WOMEN; POSTMASTECTOMY LYMPHEDEMA; PNEUMATIC COMPRESSION; DECONGESTIVE THERAPY; SYMPTOMS; TRIAL; RISK; PAIN